Bene rotunda et globosa ueritas: Epithets of Truth in Parmenides DK28 B1.29 (Revista Archai, 2019)
This article will discuss the three existing variants (Îµá½Ï†ÎµÎ³Î³ÎÎ¿Ï‚, Îµá½Ï€ÎµÎ¹Î¸ÎÎ¿Ï‚ and Îµá½ÎºÏ…ÎºÎ»ÎÎ¿Ï‚) of the adjective that qualifies á¼€Î»Î·Î¸ÎµÎ¯Î· in Parmenides fr. DK28 B1.29, focusing particularly on the latter of the three. Some editors have mantained Îµá½ÎºÏ…ÎºÎ»ÎÎ¿Ï‚, firstly because, ever since Diels, it has been considered the lectio difficilior, secondly because it is the word transmitted by Simplicius, a well reputed source of Parmenides’ Poem, and lastly because of the relationship that emerges between this reading and the image of the sphere in fragment B8. This article offers an analysis of the adjective Îµá½”ÎºÏ…ÎºÎ»Î¿Ï‚ and of its significance in archaic Greek poetry and concludes by giving a possible answer to the question why the goddess might have described truth as “well rounded.”